Pingchuanning decoction attenuates airway inflammation by suppressing autophagy via phosphatidylinositol 3‐kinase/protein kinase B/mammalian target of rapamycin signaling pathway in rat models of asthma. Issue 3 (27th September 2018) - Wang, Xinheng; Gao, Yating; Yang, Qinjun; Fang, Xiangming; Li, Zegeng
Abstract: Background: Pingchuanning decoction is a well‐known traditional Chinese medicine for the treatment of airway inflammatory diseases, including asthma. However, the potential mechanism by which Pingchuanning decoction contributes to the amelioration of airway inflammation remains unknown. Methods: A rat model of asthma was well established by inducing ovalbumin. Lipopolysaccharide‐stimulated rat tracheal epithelial (RTE) cells were used as cellular model. Lung histopathology and goblet cell hyperplasia were assessed by hematoxylin‐eosin (HE) and periodic acid Schiff staining, respectively. Total inflammatory cells count and RTE cell apoptosis were analyzed by flow cytometry. The autophagic activities were evaluated by immunohistochemical and immunofluorescence analysis and Western blot analysis of autophagy‐related proteins. We also detected the effects of Pingchuanning decoction on phosphatidylinositol 3‐kinase/protein kinase B/mammalian target of rapamycin (PI3K/Akt/mTOR) and high‐mobility group box 1 (HMGB1)‐mediated toll‐like receptor 4 (TLR4)/NF‐κB pathways‐related proteins and inflammatory cytokines using the Western blot analysis and enzyme‐linked immunosorbent assay. Results: Pingchuanning decoction effectively attenuated pulmonary pathology and autophagy. Treatment with Pingchuanning decoction activated PI3K/Akt/mTOR pathway and inhibited HMGB1/TLR4/NF‐κB pathway, which could be overturned by LY294002, a PI3K antagonist, or rapamycin (Rapa), an autophagy inducer. Conclusion: Pingchuanning decoction exerted a therapeutic effect on asthma by inhibiting autophagy via PI3K/Akt /mTOR signaling pathway. Abstract : Pingchuanning decoction exerted a therapeutic effect on asthma by inhibiting autophagy via phosphatidylinositol 3‐kinase/protein kinase B/mammalian target of rapamycin signaling pathway.